Analisis Impedansi Elastik untuk Memprediksi Jenis Litologi Batuan dan Penyebaran Kandungan Fluida (Studi Kasus Lapangan MNWP– Pertamina DOH JBB) - P., M. Nurdin W.; Yuliyanto, Gatot (JURNAL SAINS DAN MATEMATIKA, 2007)
ABSTRACT--- An identification of fluid contents on oil and gas exploration field has to be applied to determine a hydrocarbon and develop production area. This is caused a bright spot method that is based on associated with gas from seismic section, as a hydrocarbon indicator is failure, thus need an alternative method to determine the hydrocarbon from fluid contents. The identification of fluid contents are carry out on ‘MNWP’ field from inline 1380 – 1490, crossline 5040 – 5720, time 100 – 2000 millisecond with 9 well log data and use 2 software i.e. PG 2.0 Probe 3D and Vanguard. The identification involves elastic impedance analysis to find low impedance on Parigi Formation and to lithology prediction from the formation as a reservoir layer. The analysis result of elastic impedance describes that on Parigi Formation is covered by carbonate and discover fluid contents distribution be oriented from south to north that process sedimentation appropriate.Keywords: seismic section, fluid contents, impedance analysis